Normothermic Regional Perfusion for Controlled Donation After Circulatory Death: A Technical Complication During Normothermic Regional Perfusion. Issue 1 (January 2020) - Brogi, Etrusca; Circelli, Alessandro; Gamberini, Emiliano; Russo, Emanuele; Benni, Marco; Pizzilli, Giancinto; Agnoletti, Vanni
Abstract : Organ retrieved from donors after circulatory deaths (DCD) is vulnerable of the effects of warm ischemia with important consequence on graft survival and posttransplant outcome. Preservation techniques, such as normothermic regional perfusion (NRP), can be used to reduce the effects of the cardiac arrest and to generate a continuous flow to the organs, resulting in a better preservation of the organs for transplantation. However, technical complications may occur during NRP which can compromise the retrieve of donors' organs. We present a case report of a technical complication arisen during an NRP for DCD. During the extracorporeal circuit, we observed a dramatical decrease in the blood flow with excessive negative inlet pressure. It was because of a later recognized venous cannula malposition. In fact, we did not perform the radiological control for wire position. As a consequence, our clinical practice was modified. Currently, a radiological control of the wire is performed before the insertion of the catheter. Even if the donation was accomplished successfully, we reckon that it is fundamental to describe the technical issue that may occur during perfusion technique in order to improve the safety and the effectiveness of these procedures.